PERTUMBUHAN EKONOMI DAN PENGANGGURAN: VALIDITAS HUKUM OKUN DI INDONESIA - Dyan Ari Iswanto; Ghozali Maski (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study tested the validity of Okun's law in the Indonesian economy by using the difference version of Okun's law to get Okun coefficient. Moreover, the causality test was also conducted to determine the direction of the relationship variables of economic growth and unemployment. By using the Ordinary Least Square (OLS) analysis and Granger Causality Test it was concluded that the Okun's law proved to be invalid in the indonesian economy as Okun coefficient significance level is quite small. But economic growth variables shown to affect the unemployment variable statistically. Keywords: Economic Growth, Unemployment, Okun's Law, Granger Causality